THE DEFENSE OF ORAL INTERACTION IN THE MIDST OF WHATSAPP USE IN THE LEARNING ENVIRONMENT - Fernandes Arung (Journal of English Education, 2018)
This research aimed to explain the defense of oral interactions in the presence of information and communication technologies such as WhatsApp (WA) as well as to explore some of the positive contributions of WA used in building the Real Life Communication especially in the learning environment. By applying the Exploratory design, this research involved 4 participants from various educational backgrounds as a purposively selected data source indicated as WA users at once. Data were collected through Focus Group Discussion, Interview, and Observation and analyzed by several stages i.e. data reduction, displaying data, categorizing, and verifying and concluding. The results showed that oral interactions can decrease both in the language community and learning environment as the dominant use of WA that is not wise. Nevertheless, the use of WA applications also had some positive contributions in building a real relationship. Finally, the assumption that the negative impact of using the WA application should be able to change the mindset and positive attitude of the scholars in initiating and defending an oral interaction in the learning environment.